Why Kant’s Moral–Religious Project Was Bound to Unravel - Jaeha Woo (Religions)
After criticizing the three traditional proofs of divine existence in the first Critique, Kant fills this void with an apologetic argument based on his practical philosophy. However, this moral–religious project has long been charged with various inconsistencies, particularly regarding the tension between the demand for moral perfection and human limitation. There is even some indication that he becomes aware of these issues, as he later moves away from the vision of endless moral progress that holds his original project together. However, this revision does not resolve all the tensions, as the question of how imperfect humans can be well-pleasing to God remains. I argue that this predicament is a difficult-to-avoid feature of his project given how it interacts with his religious context of Lutheran Christianity. This is because he incorporates some of its elements (particularly its uncompromising moral standard) virtually intact while radically altering others (such as vicarious atonement and imputation of alien righteousness). However, this procedure undermines the coherence of the tradition he inherits because the elements he fully incorporates are meant to lead to the traditional doctrines he leaves behind. I conclude by reflecting on how theists who are sympathetic to Kant should lead his moral–religious project out of its current precarious predicament.